2016
DOI: 10.1037/xhp0000256
|View full text |Cite
|
Sign up to set email alerts
|

Optic flow speed modulates guidance level control: New insights into two-level steering.

Abstract: Responding to changes in the road ahead is essential for successful driving. Steering control can be modeled using 2 complementary mechanisms: guidance control (to anticipate future steering requirements) and compensatory control (to stabilize position-in-lane). Drivers seem to rapidly sample the visual information needed for steering using active gaze patterns, but the way in which this perceptual information is combined remains unclear. Influential models of steering capture many steering behaviors using jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…The following prefilter dynamics are consistent with the estimated FRFs in Fig. 5, and are identical to the preview model of [29], [30]: (10) with K f the scaling gain, T l,f the low-pass (smoothing) filter time-constant, 1 and τ f the look-ahead time.…”
Section: ) Preview Response Dynamicssupporting
confidence: 69%
See 3 more Smart Citations
“…The following prefilter dynamics are consistent with the estimated FRFs in Fig. 5, and are identical to the preview model of [29], [30]: (10) with K f the scaling gain, T l,f the low-pass (smoothing) filter time-constant, 1 and τ f the look-ahead time.…”
Section: ) Preview Response Dynamicssupporting
confidence: 69%
“…2 For the data in Fig. 9, the standard deviation of the vehicle's lateral position deviation from the centerline σ y e ≈ 0.1 m, which is sufficiently low for safe lane keeping on most roads; measured deviations on real roads are typically higher [10], because the current model analysis lacks external disturbances (y d , ψ d ) and human remnant (n).…”
Section: A Feedforward Control: Preview Prefiltermentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, although the path may be occluded, participants can still get visual feedback, in the form of optic flow, regarding how their steering actions move them through the environment. Others have demonstrated that biased optic flow can influence steering Kountouriotis, Mole, Merat, & Wilkie, 2016;Mole, Kountouriotis, Billington, & Wilkie, 2016), though in those studies path information was continuously available. Here, the selective manipulation of path occlusion and optic flow enabled us to experimentally control the information that was available to the driver.…”
Section: Visual Information For Steeringmentioning
confidence: 99%